OCA/OCP Oracle database 12c all-in-one exam guide (exams 1Z0-061, 1Z0-062, & 1Z0-063) - Watson, John; Ramklass, Roopesh; Bryla, Bob (Oracle Press, 2015)
Including examples; practice questions; chapter summaries; and a two-minute drill to reinforce essential knowledge in each chapter; this Oracle Press guide covers all of the exam objectives on the Installation and Administration; SQL Fundamentals; and Advanced Administration exams in detail. --
Includes index. - Includes bibliographical references. - Description based on print version record
Keywords: Oracle (Computer file); SQL (Computer program language) -- Study guides -- Examinations; Relational databases -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; SQL (Langage de programmation); Examens; Guides de l'étudiant; Bases de données relationnelles; Examens; Guides de l'étudiant; Electronic data processing personnel; Certification; Relational databases; Examinations; Study guides